Readers are ReadingManagement by Policy: How Companies Focus Their Total Quality Efforts to Achieve Competitive Advantage, by CollinsBrendan and HugeErnest. Milwaukee, WI: ASQC Quality Press, 1993.The Logic of Organizations, by AbrahamssonBengt. Newbury, CA: Sage, 1993.The Vulnerable Fortress: Bureaucratic Organization and Management in the Information Age, by TaylorJames R. and Van EveryElizabeth J.. Toronto, Canada: University of Toronto Press, 1993.Shogun Management: How North Americans Can Thrive in Japanese Companies, by ByhamWilliam C. and DixonGeorge. New York: Harper Business, 1993.Scenario-Driven Planning: Learning to Manage Strategic Uncertainty, by GeorgantzasNicholas C. and AcarWilliam. Westport, CT: Quorum Books, 1994.The Globalization of Business, by DunningJohn H.. London: Routledge, 1993. - Helms, Marilyn M.; Swanson, Diane L.; Giroux, Nicole; Helms, Marilyn M.; Ensign, Prescott C.; Prasad, S. B. (Academy of Management Review, 1994)
The article presents a list of books, which readers are reading. They include “Management by Policy: How Companies Focus Their Total Quality Efforts to Achieve Competitive Advantage,” “The Logic of Organizations,” and “The Vulnerable Fortress: Bureaucratic Organization and Management in the Information Age.”